Efficient visible-light-driven H2 evolution over sol-gel processed Bi2WO6 nanocrystals anchored with Ag2O support. (1st May 2023) - El-Shishtawy, Reda M.; Shawky, Ahmed; Alorfi, Hajer S.; Hussein, Mahmoud A.; Mohamed, Reda M.
Abstract: Hydrogen (H2 ) is regarded as the future supernumerary energy source owing to its lightweight, renewability and greenness. The interest in the photocatalytic hydrogen (H2 ) evolution over semiconductor photocatalysts has become a robust approach for green fuel production. In the meantime, bismuth tungstate (Bi2 WO6 ) is considered a promising photocatalyst for H2 evolution. This work studied the synthesis and improvement of nanocrystalline Bi2 WO6 via a modified sol-gel process followed by anchoring diverse trace portions of silver oxide (Ag2 O) support. The prepared nanostructures were utilized for the photocatalytic evolution of H2 under visible-light irradiation in a water/glycerol mixture. The detailed depiction of the gained photocatalysts exposed the synergetic effects of anchoring Ag2 O on the light harvesting and semiconducting properties without significant changes to the main surface or crystalline structure. The addition of 3.0 wt% Ag2 O on Bi2 WO6 has a little reduction on its specific surface area from 145 to 125 m 2  g −1 . However, visible light absorbance improved due to its bandgap energy reduction from 2.78 to 2.31 eV. The 3% Ag2 O/Bi2 WO6 utilization at the optimized dose of 2.0 gL ‒1 led to efficient H2 generation in the presence of Pt deposits of 3.06 mmol g −1 h −1 that sustained a 97% reusability five times. This capable H2 evolution is credited to the extended light harvesting and the robust charge separation by Ag2 O anchoring to Bi2 WO6 . Graphical abstract: Image 1